Rural Women Power, Effects and Role in Farm Management and Decision Making in North Kordofan State-Sudan - Gaafar B. Suliman,; Mohammed Y.Abdalla,; Manal Hussain Mohammed Eltigani,; Elzubair E. Elzain,; Maruod E. Maruod, (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study was conducted in Um Rowaba and Bara localities of North Kordofan State during 2013/2014 cropping season. The objectives of the study were to assess the role of rural women in farm management and decision making in crop production. The primary data was collected via structured questionnaire using stratified simple random sampling techniques; the samples of the village were selected randomly in each administrative unit in both localities, hence. 20 villages were selected; and 6 persons were collected from each village. The secondary data was obtained from the reports and literature. Data were analyzed via descriptive statistics, tables of frequencies and cross-tabulation. Chi-square was used to test the association between the variables. Study results showed that certain socio-economic factors encourage women farmer to participate positively in farm management decision making. Study results revealed that, 32.5% of the respondents were married and 28% were not married while 20.8% were widows and 18.3% were divorced that. 31.7% were woman headed household. 50.8% of the respondents were illiterates while 26.7% had attended basic education, and 22.5% had attended secondary education and this indicates that most of women farmers were facing illiteracy problem which inhabit them to attend class training. 35% of the respondents were members in community organization. 77.8% of the respondents who attended secondary school level make the final decision, and followed by 56.3% respondents who attended basic school level followed by 44.3% of illiterate respondents make the final decision. The result of chi-square revealed that education level of women farmers significantly (p<0.01) influence their role in decision making in allocating area for cultivation.  Three-quarter of women who attended secondary education and half of women who attended basic education make final decision compared to lesser percentages of illiterate women. The results of chi-square revealed that the state of land ownership has no influence on participation of women in decision making in area allocation for cultivation, for these difference were not significant (p>0.05).  The results of chi-square revealed that the age of women significantly (p<0.01) influence their role in decision making in type of crops to be grown. The results of chi-square revealed that educational level of women farmers significantly (p<0.01) influence their role in decision making in type of crop to be grown.